Severe Perinatal Hypoxic-Ischemic Brain Injury Induces Long-Term Sensorimotor Deficits, Anxiety-Like Behaviors and Cognitive Impairment in a Sex-, Age- and Task-Selective Manner in C57BL/6 Mice but Can Be Modulated by Neonatal Handling - Muntsant, Aida; Shrivastava, Kalpana; Recasens, Mireia; Giménez-Llort, Lydia (Frontiers in Behavioral Neuroscience, 2019)
Perinatal brain injury leads to neurological disabilities throughout life, from motor deficits, cognitive limitations to severe cerebral palsy. Yet, perinatal brain damage has only found limited therapeutic outcomes. Besides, the immature brain of premature children is at increased risk of hypoxic/ischemic (HI) injury, with boys being more susceptible to it and less responsive to protective/therapeutical interventions. Here, we model in male and female C56BL6 mice, the impact of neonatal hypoxia/ischemia (HI) and the protective effects of neonatal handling (NH), an early life tactile and proprioceptive sensory stimulation. From postnatal day 1 (PND1, modeling pre-term) to PND21 randomized litters received either NH or left undisturbed. HI brain damage occurred by permanent left carotid occlusion followed by hypoxia at PND7 (modeling full-term) in half of the animals. The behavioral and functional screening of the pups at weaning (PND23) and their long-term outcomes (adulthood, PND70) were evaluated in a longitudinal study, as follows: somatic development (weight), sensorimotor functions (reflexes, rods and hanger tests), exploration (activity and open-field test), emotional and anxiety-like behaviors (corner, open-field and dark-light box tests), learning and memory (T-maze and Morris water-maze). HI induced similar brain damage in both sexes but affected motor development, sensoriomotor functions, induced hyperactivity at weaning, and anxiety-like behaviors and cognitive deficits at adulthood, in a sex- and age-dependent manner. Thus, during ontogeny, HI affected equilibrium especially in females and prehensility in males, but only reflexes at adulthood. Hyperactivity of HI males remitted at adulthood. HI increased neophobia and other anxiety-like behaviors in males but emotionality in females. Both sexes showed worse short/long-term learning, but memory was more affected in males. Striking neuroprotective effects of NH were found, with significantly lower injury scores, mostly in HI males. At the functional level, NH reversed the impaired reflex responses and allowed better performances in hippocampal-dependent spatial-learning tasks, also especially in males. Finally, neuropathological correlates referred to atrophy, neuronal densities and cellularity in the affected areas (hippocampus, caudate/putamen, thalamus, neocortex and corpus callosum) point out distinct neuronal substrates underlying the sex- and age- functional impacts of these risk/protection interventions on sensorimotor, behavioral and cognitive outcomes from ontogeny to adulthood.